Analysis of Students’ Need and Perception on Integrated Natural Science Worksheet based on Contextual Teaching and Learning - Nur Inayah Syar; Sulistyowati Sulistyowati (Elementary: Jurnal Ilmiah Pendidikan Dasar, 2021)
Abstract Students’ worksheet is one kind of teaching material that can assist the students to learn independently especially in distance learning during the pandemic. Before developing the workheet, need analysis is required to dig the need, attractiveness, and type of worksheet needed by the students. This research aims to analyze the need of students’ worksheet on Natural Science Study and Learning Course and to find out the students’ perception on CTL based worksheet. This research was a quantitative research by using survey method. Total samples were 52 students divided into two groups and the research instrument used was questionnaire. The research results show that based on the need analysis, 70% students of PGMI Study Program needed worksheet in the natural science practice, 60% students were interested to use CTL based worksheet. Beside that the students need worksheet which in it there is case or real example in daily life, illustration, short material, and summary. The students’ perception on CTL based worksheet is in excellent category with percentage 92,63%. Keywords: Worksheet, CTL, Needs Analysis, Perception Abstrak Lembar Kerja Mahasiswa (LKM) merupakan salah satu jenis bahan ajar yang dapat membantu mahasiswa belajar secara mandiri terutama dalam pembelajaran jarak jauh di masa pandemi. Sebelum mengembangkan LKM perlu adanya analisis kebutuhan guna menggali kebutuhan, ketertarikan dan jenis LKM yang dibutuhkan mahasiswa. Penelitian ini bertujuan untuk menganalisis kebutuhan LKM bagi mahasiswa pada mata kuliah Kajian dan Pembelajaran IPA dan untuk mengetahui persepsi mahasiswa terhadap LKM berbasis CTL. Penelitian ini merupakan penelitian kuantitatif dengan menggunakan metode survei. Total sampel yaitu 52 orang mahasiswa yang terbagi menjadi dua kelompok dan instrumen penelitian yang digunakan berupa angket. Hasil penelitian menunjukkan bahwa berdasarkan analisis kebutuhan, 70% mahasiswa Prodi PGMI membutuhkan LKM dalam praktikum IPA, 60% mahasiswa tertarik menggunakan LKM berbasis CTL. Selain itu mahasiswa membutuhkan LKM yang di dalamnya terdapat kasus dan contoh nyata dalam kehidupan sehari-hari, ilustrasi, materi singkat dan rangkuman. Persepsi mahasiswa terhadap LKM berbasis CTL berada pada kategori Sangat Baik dengan persentase 92,63%. Kata kunci: LKM, CTL, Analisis Kebutuhan, Persepsi